IMPLEMENTING OF LEADERSHIP, WORK CULTURE AND ORGANIZATIONAL CLIMATE TOWARDS EMPLOYEE PERFORMANCE OF THE MINISTRY OF RELIGIOUS AFFAIR EAST JAVA PROVINCE - Firdiana, Erma; Pompong B. Setiadi (Dinasti International Journal of Digital Business Management, 2022)
One of the factors that often occurs in employees is the problem of performance. The decision made by the employee is annulled not only by one party. But there is a form of contribution from other aspects or elements that affect the intensity of performance, whether high or low. In this case, Ministry of Religious Affair East Java Province and civil servants are elements that need to work together in determining the capacity of a work decision that has a relatively high capacity. Lack of performance on employees in the form of self-confidence in employees which results in a decrease in organizational performance. In terms of performance, a government bureaucracy becomes satisfaction in recruiting companies and reviewing from the integrity aspect of institutions that have performance and avoid negative impacts such as burnout, lack of attendance, and increased work inaction in determining decisions. In this study, the increase in performance is based on work culture, and organizational climate factors. The intensity of motivation that is classified as high has an impact on high performance. The high two of conceptual will have an impact on the high performance of employees. The more employees show high work motivation, then at that time performance are formed by themselves. The influence on motivation is one of the factors on individual characteristics, especially in terms of the work environment. Meanwhile, the formation of a person's behavior has the characteristics of the cause of a motivation by the desire to get a certain achievement and becomes a form of modality in the need to fulfill a life goal. If the goal in need seems urgent, then the individual will act or respond through a response with other individuals who need it the same. Thus, the individual integrates and strives together through mutually beneficial interactions or relationships.